Protein nanopores with covalently attached molecular adapters. - Wu, H; Astier, Y; Maglia, G; Mikhailova, E; Bayley, H (2007)
Molecular adapters are crucial for the stochastic sensing of organic analytes with alpha-hemolysin (alphaHL) protein nanopores when direct interactions between analytes and the pore cannot readily be arranged by conventional protein engineering. In our earlier studies, cyclodextrin adapters were lodged noncovalently within the lumen of the alphaHL pore. In the present work, we have realized the controlled covalent attachment of a beta-cyclodextrin (betaCD) adapter in the two possible molecular orientations inside alphaHL pores prepared by genetic engineering. There are two advantages to such a covalent system. First, the adapter cannot dissociate, which means there are no gaps during stochastic detection, a crucial advance for single-molecule exonuclease DNA sequencing where the continuous presence of a molecular adapter will be essential for reading individual nucleotides. Second, the ability to orient the adapter allows analytes to bind through only one of the two entrances to the betaCD cavity. We demonstrate that the covalently attached adapters can be used to alter the ion selectivity of the alphaHL pore, examine binding events at elevated temperatures, and detect analytes with prolonged dwell times.